PANCASILA STATE CONCEPT AS DARUL AHDI WA SHAHADAH (STUDY ON MUHAMMADIYAH REGIONAL LEADERS OF MEDAN CITY) - Hasanuddin Hasanuddin; Nurman Ginting (Proceeding International Seminar of Islamic Studies, 2022)
This research aims to examine the understanding of the concept of Darul Ahdi Wasyahadah at the Regional Leader of Muhammadiyah City of Medan, While the object of this research is the elements of the leadership in the Regional Leader of Muhammadiyah City of Medan. The formulation of this research problem is how to understand the Concept of Pancasila State as Darul Ahdi Wasyahadah at the Regional Leader of Muhammadiyah City of Medan. For research methods using a qualitative approach with the type of case study research at the Regional Leader of Muhammadiyah City of Medan. The results of this study reveal that the Concept of Pancasila State as Darul Ahdi Wasyahadah can be well understood by the leadership elements in the Medan City PDM, and the understanding of the concept has been done for muhammadiyah cadres and sympathizers in medan city in every pdm work program of Medan city. It's just that planned and programmable activities administratively have not been planned properly so that the achievements. Keyword: Pancasila State, Darul Ahdi Wa Shahadah, Muhammadiyah